The Effect of Career Development, Work Motivation and Competence on Employee Performance at PT. Bumi Menara Internusa Cirebon - Siti Faizah; Ni’matun Hasana; Dharliana Hardjowikarto; Sunimah Sunimah (Interdisciplinary Social Studies, 2025)
In today’s competitive global business landscape, optimizing employee performance is essential to sustaining organizational success. However, many companies in Indonesia, including PT. Bumi Menara Internusa Cirebon, face performance challenges due to limited career development programs, inconsistent work motivation, and varying employee competencies. This study aims to examine the influence of career development, work motivation, and competence on employee performance. A quantitative research method was employed using associative analysis with a sample of 142 employees, selected through the Slovin formula. Data were collected via structured questionnaires and analyzed using SPSS 22, including validity tests, reliability tests, multiple linear regression, t-tests, F-tests, and determination coefficient analysis. The results show that both career development and competence have a significant positive effect on employee performance, while work motivation does not have a significant effect. Collectively, the three variables account for 56.4% of the variance in performance outcomes. These findings underscore the importance of investing in structured career development and competence-building initiatives, while reevaluating motivational strategies. The study provides actionable insights for HR managers seeking to enhance employee productivity through targeted human capital interventions.